Zein Nanoparticles Improve the Oral Bioavailability of Curcumin in Wistar Rats - Ana Brotons-Canto; Carlos J. González-Navarro; Ana Gloria Gil; Eduardo Asin-Prieto; María José Saiz; Josep Manuel Llabrés (MDPI AG, 2021)
Curcumin is a natural compound obtained from turmeric root with high antioxidant and anti-inflammatory activities. However, clinical application of curcumin has been limited due to its low solubility and bioavailability and rapid metabolism and degradation. This study was conducted to evaluate the effect of curcumin incorporation in zein nanoparticles on the pharmacokinetic parameters of systemic curcumin in plasma. Wistar rats were administered a single oral dose of 250 mg/kg of standard curcumin (control) or nanocurcumin (zein-based nanoparticles, Nucaps). The proposed new formulation was also compared with two commercially available curcumin complexes. Blood samples were collected at different times, and plasma levels were determined using HPLC-MS/MS. Overall, nanocurcumin (Nucaps) formulation was well tolerated and showed a 9-fold increase in oral bioavailability when compared to the standard curcumin natural extract. In addition, the nanoparticles prepared in this study demonstrated a bioavailability profile superior to that of other bioavailability-enhanced curcumin complexes currently available in the marketplace. Thus, our nanoparticle-based formulation has shown great potential as a nutraceutical for the oral administration of curcumin.